Circumscribed, congenital and persistent alopecia of the scalp. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2018)
At birth or in the first weeks of life, hair may lack within a more or less large but always circumscribed area of the scalp and this sign indefinitely persists throughout life. The four diseases which can be responsible for this sign are, in decreasing order of frequency, sebaceous nevus, triangular alopecia, aplasia cutis and pseudopelade associated with some genetic disorders, above all incontinentia pigmenti. Let us define these four different conditions. (...).